Authenticity and creativity: The development of pencak silat in Sumedang - Semiarto Aji Purwanto; Andi R Saputra (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2020)
Many studies of silat have documented the jurus (moves) or aliran (streams) in silat, especially those based on tradition.Even so, there are still many things about this martial arts tradition that have not been deeply touched, for instance, how it can be developed without losing the authenticity of the tradition. We exercise it as a problem of how tradition and change should be defined, how authenticity is placed in a dynamic context, and how silat practitioners continue their creativity. Within an anthropological perspective, we put forward the case of the Perguruan Silat Garuda Putih in Sumedang to study how the individual ideas, learning process, and creations; and authenticity, structure, and power are tied together. The Sumedang silat tradition which originated from various aliran has been structured as a unique gaya (style) of fighting. The role of perguruan (silat training center), systematically keeps a beginner in silat to learn standard silat. At the end of learning, however, we believe that the process of creating moves and ibing (opening movements) shows a high dynamic amidst creativity, aligning movements with standards, maintaining authenticity, but at the same time also marking the individual characteristics of students.